Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Komunikasi Matematis Siswa Kelas VII SMP - Putra, Aji Permana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2024)
Based on the results of interviews before the research, it showed that students' mathematical communication skills were still weak. For example, in square material, students cannot convey their arguments well, even though the ideas and concepts are already in their heads. Apart from that, students have difficulty interpreting assignments in the form of pictures, and students' ability to solve story problems is still weak, they have difficulty translating problem sentences into mathematical models and solving them according to the storyline. Meanwhile, square material is closely related to everyday life, therefore most of the questions are in the form of stories. This research is field research with a posttest only control design. The population of this study were all class VII students at SMPN 2 Ceper, Klaten Regency, consisting of seven classes with a total of 224 students. Cluster random sampling. Used for sampling. Based on sampling, it is known that class VIIA is the research experimental class (PBL Model) and class VIIB is the control class (Conventional Learning Model). Data collection methods include interviews, documentation and tests. Data analysis includes preliminary analysis, test instrument analysis, and final stage analysis. After the hypothesis is tested, the researcher uses the right-sided measured difference test (t-test). Based on the t test calculation and the significance level, the value obtained because H0 is rejected. This means that the average mathematical communication ability of the experimental class (using the PBL model) is better than the average mathematical communication ability of the control class. From this description it can be concluded that the problem-based learning (PBL) model is effective for students' mathematical communication skills on the main material of quadrilaterals in the even semester of class VII SMPN 2 Ceper in the 2023/2024 academic year.